Inter-annual sea level change and transgression along a barrier Island coast - Zarillo, Gary A. (Frontiers in Environmental Science, 2023)
On the decadal time scale of coastal planning and management, relative sea-level rise is usually considered a trend or constant rate rather than a dynamic, time varying influence on coastal change. However, the coastal ocean sea level along the east coast of Florida and coastal regions further north is, to a first order, controlled at the interannual and decadal time scale by the dynamics of North Atlantic circulation and Gulf Stream (GS) flow, Every coastal region has its own distinctive annual sea-level cycle, and longer-term intra- and inter-decadal sea-level oscillations. This paper addresses the influence of the strong Florida coastal ocean sea-level signal on topographic evolution of the shoreface, coastal sediment budgets, and potential for coastal transgression at the decadal time scale.